Рейд на Сан и Вислу - Вершигора Петр Петрович (Правда, 1990)
Экземпляры: к/х (ретроконверсия) / Инвентарный номер: 28884 / Цена: 2.10 / Сис.шифр: Р2 / Авт.знак: В 37 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6